2018
DOI: 10.1186/s40510-018-0213-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of changes due to mandibular autorotation following miniplate-anchored intrusion of maxillary posterior teeth in open bite cases

Abstract: BackgroundPrediction of the treatment outcome of various orthodontic procedures is an essential part of treatment planning. Using skeletal anchorage for intrusion of posterior teeth is a relatively novel procedure for the treatment of anterior open bite in long-faced subjects.MethodsData were analyzed from lateral cephalometric radiographs of a cohort of 28 open bite adult subjects treated with intrusion of the maxillary posterior segment with zygomatic miniplate anchorage. Mean ratios and regression equations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The increase in overbite of 1.2 mm per 1 mm of maxillary molar intrusion in the present study was smaller than that in previous studies, which reported a 2–3 mm increase in overbite. 26 - 29 This discrepancy may be attributed to the data interpretation methods, as simple ratios and linear regressions can be differently interpreted. The coefficient for maxillary molar intrusion in the present study was close to that in previous studies that showed an overbite increase of 1.5 mm 26 and 1.2 mm 28 per 1 mm of additional maxillary molar intrusion.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in overbite of 1.2 mm per 1 mm of maxillary molar intrusion in the present study was smaller than that in previous studies, which reported a 2–3 mm increase in overbite. 26 - 29 This discrepancy may be attributed to the data interpretation methods, as simple ratios and linear regressions can be differently interpreted. The coefficient for maxillary molar intrusion in the present study was close to that in previous studies that showed an overbite increase of 1.5 mm 26 and 1.2 mm 28 per 1 mm of additional maxillary molar intrusion.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, palatal mini-implants have gained popularity and have been widely used for molar intrusion, molar protraction, segment protraction, and anterior tooth retraction [ 1 7 ]. The palatal mini-implants are usually preferred, because the site of mini-implant placement is easily accessible, has less soft tissue irritation, does not interfere with the desired orthodontic tooth movement, and has good quality and quantity of bone [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment protocols involve the use of fixed appliances, orthognathic surgery, temporary anchorage devices with mini-screws or mini-plates, aligners, headgears, bite blocks [2][3][4][5][6][7][8][9]. Vela-Hernández et al [7] reported that build-ups on posterior teeth are an efficient tool for AOB treatment in adults, as they act in a similar way to bite blocks by promoting a mandibular rotation.…”
Section: Introductionmentioning
confidence: 99%